STRESS ANALYSIS OF HEAVY DUTY TRUCK CHASSIS AS A PRELIMINARY DATA FOR ITS FATIGUE LIFE PREDICTION USING FEM (Jurnal Mekanikal, 2018)
This paper presents the stress analysis of heavy duty truck chassis. The stress analysis is important in fatigue study and life prediction of components to determine the critical point which has the highest stress. The analysis was done for a truck model by utilizing a commercial finite element packaged ABAQUS. The model has a length of 12.35 m and width of 2.45 m. The material of chassis is ASTM Low Alloy Steel A 710 C (Class 3) with 552 MPa of yield strength and 620 MPa of tensile strength. The result shows that the critical point of stress occurred at the opening of chassis which is in contact with the bolt. The stress magnitude of critical point is 386.9 MPa. This critical point is an initial to probable failure since fatigue failure started from the highest stress point.
Keywords: Stress analysis; fatigue life prediction; truck chassis